2021
DOI: 10.1021/acs.macromol.0c02677
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thiol Substitution on the Kinetics and Efficiency of Thiol-Michael Reactions and Polymerizations

Abstract: The kinetic effects of the substitution and functionality of the thiol in thiol-Michael reactions were investigated using model monofunctional thiols and multifunctional thiols used in various cross-linking polymerizations. The differences in kinetic rates and final conversions were observed via Fourier transform infrared spectroscopy. The shelf life of these polymers and their mechanical properties were analyzed using a rheometer to measure viscosity changes over time. It was concluded that for monofunctional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 25 publications
0
23
1
Order By: Relevance
“…Maleimide and its derivatives have been used extensively to modify cysteine residues [ 5 , 25 ]. The advantage of cysteine modification by maleimide is its high selectivity and irreversibility [ 22 , 109 ]. However, in comparison to, for example methanethiosulfonate, the reaction is slower and the reaction of cysteine with maleimides requires the monitoring of pH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maleimide and its derivatives have been used extensively to modify cysteine residues [ 5 , 25 ]. The advantage of cysteine modification by maleimide is its high selectivity and irreversibility [ 22 , 109 ]. However, in comparison to, for example methanethiosulfonate, the reaction is slower and the reaction of cysteine with maleimides requires the monitoring of pH.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the reaction rate is influenced by the steric hindrance of the reactants; the presence of larger substituents in the α and β positions on the Michael acceptor can hamper the reaction [20,21]. Moreover, a high steric hindrance around the nucleophilic center decreases its reactivity to the Michael acceptor [22]. In 2004 Ren et al [23] developed a simple strategy for specifically targeting cysteinecontaining peptides in a tryptic digest.…”
Section: Cysteine-containing Peptide Enrichment In Solution 21 Michae...mentioning
confidence: 99%
“…More precisely, these ionogels were obtained from the reaction of multifunctional thiols on diacrylate using thiol-ene Michael addition chemistry in the presence of ILs. The thiol-ene Michael addition is a reaction that involves a base- or nucleophile-catalyzed addition of a thiolate anion to electron-deficient alkenes such as maleimides, vinyl sulfones, acrylates, and methacrylates [ 7 ]. The sole difference between base- and nucleophile-catalyzed reactions lies in the way the thiolate anion is generated.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 While substantial work has been done to characterize TTE for thiols common in materials synthesis, 5 the effect of substitution of the thiol on TTE has received little attention. Recently, the substitution of the thiol on various thiol−X processes has seen attention from Li and co-workers, who observed that increasingly substituted thiols have a longer shelf life and less odor than typical primary thiols, 14 and Long and co-workers, who have shown that secondary and tertiary thiols can be used in thiol-ene 15 and thiol−Michael addition 16 polymerizations with minimal detrimental effects on reaction kinetics or conversion at relevant polymerization conditions while resulting in the improved shelf life of the resin mixture. This outcome has important implications for many thiol−X materials that often cannot be premixed and stored as a monomer resin due to their high reactivity.…”
Section: ■ Introductionmentioning
confidence: 99%